Catch analysis of the lessepsian fish species in Banias coast-Syria - حسن محمد; علي عبد اللطيف; الشيخ احمد علاء (Latakia University Journal -Biological Sciences Series, 2021)
The aim of this study is to shed light on fish catch in Banias port through analyzing catches of / 15 / homogeneous fishing boats, to show the development of the lessepsian fish catch in this port. The boats were selected randomly and data were collected during the productive season: July 2019 to June 2020, at an average of /4/ times a month for each boat. The data were analyzed statistically to estimate the best fishing method that achieves the highest percentage of the lessepsian fish species landings within this port. The results showed that the pot-fishing method is the most feasible way to catch Lessepsian fish, and the highest percentage of the Lessepsian fish catches was during June (11.9%) . The percentage of the poisonous species in the landings was about 5.1% of the total Lessepsian fish catches. The Siganus rivulatus (Forsskal,1775) species achieved the highest percentage in the studied Lessepsian catch ( 20.1%) in Banias port during the studied period, while the marine Plotosus lineatus (Thunberg, 1787) species constituted the lowest percentage (0.6%) of the total species catch. The total quantities caught by nets over the 12 months period constituted the largest percentage within the studied catch, amounting to 52.8% of the catch achieved by the fishing methods used. The quantities caught by nets over the same 12 months period constituted the largest percentage, amounting to 64.4% of the catch achieved by the fishing methods used.